MODEL CITY BRANDING SEBAGAI STRATEGI PENGUATAN PARIWISATA LOKAL PROVINSI JAWA TIMUR - yusuf adam hilman; Krisna Megantari (Jurnal Komunikasi dan Kajian Media, 2018)
City branding strategy to strengthen is tourism, so that this effort can support the development of the, are indirectly can increase their own local revenue, that is why we need to understand the process in their entirety. Several areas in the province of East Java, such as: Banyuwangi, Lumajang, Ponorogo, Batu and Jember, can give a lesson in relation to the city branding to be relevant and according to potential as well as the construction positive image in accordance with a hoped-for goal. A method of qualitative diskriptif was used in the study, data collection technique through the results of the observation and a literature review. From the research result conducted by, obtained city branding strategy is conducted through a tagline and also make the Mascot, of main to support regional tourism promotion.